An analysis of economic indicators on the family takaful demand in Malaysia / Nurulhidayah Dani and Siti Nor Mahassan @ Mat Hussin - Dani, Nurulhidayah; Mahassan @ Mat Hussin, Siti Nor (2014)
This study is focusing on the analysis of economic indicators on the Takaful demand in Malaysia. Takaful also can be known as Islamic Life insurance. The main objective for this study is to make an analysis on what are the factors that contribute to the demand on Takaful in Malaysia. The demand that contribute for this analysis includes income, interest rate, inflation rate and stock. In gathering the data, the researchers had used secondary data which is the data were taken on the quarterly basis for the 18 years (1996-2013). Mostly, the data were taken from DataStream website of UiTM Kota Bharu campus. Besides, the data were also taken from the portal of Bank Negara Malaysia and Department of Statistics. Then, the data were analyzed using IBM SPSS Statistics 20 to analyze the Multiple Linear Regression. Then, the data had been analyzed using hypothesis testing which consists of Tstatistics, F-statistics and Durbin Watson